CoSiReT: Innovation of ReT (Refutation Texts) to Reduce Students' Misconceptions Concerning Transverse Waves - Shobrina Nurul Mufida; Achmad Samsudin; Endi Suhendi; Ida Kaniawati; Hera Novia (Postgraduate, University of Mataram, 2023)
The research goal was to develop innovative learning media on refutation texts (ReT), scilicet integrating Computer Simulations on Refutation Texts (CoSiReT). CoSiReT's role is to reduce students' misconceptions concerning the basic concept of transverse waves. This research design used 4D (Define, Design, Develop, and Disseminate). Participants include 64 students aged 16-18 years in the Tuban region, East Java, Indonesia (37 male were called Mas, and 27 female were called Mbak). The research instrument used a media validation sheet (15 assessment indicators). The pre-post test instrument used the Multi-representation of a Four-tier Instrument on Transverse Wave (MOFI-OTW). Analysis of data validation results was using a rater test assisted by Rasch's Mini-Facets software. According to the seven validators, the results of CoSiReT fulfill aspects of instructions for use, language, content presentation, and appearance. The percentage of students' misconception reduction was analyzed using the Reduction Misconceptions (RM) adapted from Hake's n-gain equation. Overall, the reduction of misconceptions is in the high category. Thus, it can be concluded that CoSiReT can be developed and used a role in reducing student misconceptions. Researchers or practitioners are expected to implement CoSiReT as a learning innovation that aims to reduce basic misconceptions of transverse waves.